2013
DOI: 10.1155/2013/854763
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Enzymatic Method for Pectin Methyl Esters Determination

Abstract: Pectin is a natural polysaccharide used in food and pharma industries. Pectin degree of methylation is an important parameter having significant influence on pectin applications. A rapid, fully automated, kinetic flow method for determination of pectin methyl esters has been developed. The method is based on a lab-made analyzer using the reverse flow-injection/stopped flow principle. Methanol is released from pectin by pectin methylesterase in the first mixing coil. Enzyme working solution is injected further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…To identify whether the increased DM in erf4 seeds was a result of decreased PME activity, total proteins were extracted from whole seeds of wild-type, erf4 , erf4-2 : 35S::ERF4 and 35S::ERF4 overexpressors, and PME activity was determined as previously described by Lekawska-Andrinopoulou et al (2013) with the average wild-type PME activity being normalized to 100% (=1). The results showed that PME activity was reduced by ~13% and ~17% in the erf4-1 and erf4-2 seeds, whereas it was elevated by 5~14% in 35S::ERF4 lines compared to wild-type (Figure 2E and F).…”
Section: Resultsmentioning
confidence: 99%
“…To identify whether the increased DM in erf4 seeds was a result of decreased PME activity, total proteins were extracted from whole seeds of wild-type, erf4 , erf4-2 : 35S::ERF4 and 35S::ERF4 overexpressors, and PME activity was determined as previously described by Lekawska-Andrinopoulou et al (2013) with the average wild-type PME activity being normalized to 100% (=1). The results showed that PME activity was reduced by ~13% and ~17% in the erf4-1 and erf4-2 seeds, whereas it was elevated by 5~14% in 35S::ERF4 lines compared to wild-type (Figure 2E and F).…”
Section: Resultsmentioning
confidence: 99%
“…Several PME genes have been identified and investigated (Tieman et al, 1992;Gaffe et al, 1997;Wen et al, 1999;Hongo et al, 2012). PMT activity has been described, and the enzyme properties characterized, in several plant species (Goubet et al, 1998;Goubet and Mohnen, 1999;Ishikawa et al, 2000;Łękawska-Andrinopoulou et al, 2013). However, functions of the PMT gene are not well understood, especially during the reproductive process.…”
Section: Introductionmentioning
confidence: 99%
“…Among the above detection techniques, spectrophotometry presents several advantages, including its flexibility to be automated using flow injection analysis (FIA) [ 12 , 13 ], methodology that has been widely used to develop analytical procedures [ 14 , 15 ]. Spectrophotometry technique allows the use of cost-effective instrumentation, such as homemade photometers, assembled using light emitting diode (LED) and photodiode [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%